Online Gambling as a Contemporary Form of Maysir: A Maqasid al-Shari'ah Analysis in Islamic Law - Gea Aurlina; Farah Dzuliska; Ahmad Anugrah Hasibuan; Yoga Al-Farizi; Ahmad Suryadi; Zahwa Anandira (Jurnal Elsyakhshi, 2025)
The rapid development of digital technology has led to the emergence of online gambling as a contemporary form of maysir, which is increasingly accessible to various segments of society, including Muslim communities. While gambling is explicitly prohibited in Islam, the transformation of maysir in digital platforms raises new juridical and ethical questions in contemporary fiqh. This study aims to analyze online gambling through the framework of maqasid al-shariah, with particular emphasis on the protection of property (hifz al-mal) and intellect (hifz al-aql). Employing a qualitative normative approach, this research is based on a critical review of classical and contemporary fiqh literature, fatwas issued by religious authorities, state regulations, and studies on the social impacts of online gambling. The findings demonstrate that online gambling poses significant threats to the fundamental objectives of Islamic law, not only by undermining individual financial security but also by contributing to intellectual and social harm. The study argues that the maqasid al-shariah approach offers a contextual and adaptive framework for addressing digital-era gambling practices and formulating more responsive Islamic legal reasoning in contemporary society.